Avian torpor or alternative thermoregulatory strategies for overwintering? - Douglas, T.; Cooper, Christine; Withers, Philip (The Company of Biologists Ltd., 2017)
© 2017 Published by The Company of Biologists Ltd.It is unclear whether torpor really is uncommon amongst passerine birds. We therefore examined body temperature and thermoregulatory strategies of an Austral passerine, the white-browed babbler (Pomatostomus superciliosus), which has characteristics related to a high probability of torpor use; it is a sedentary, insectivorous, cooperative breeding species, which we studied during winter in a temperate habitat. Wild, free-living babblers maintained normothermy overnight, even at sub-zero ambient temperatures, with a mean minimum body temperature of 38.5±0.04°C that was independent of minimum black bulb temperature. Physiological variables measured in the laboratory revealed that babblers had a lowbasalmetabolic rate and evaporative water loss, but their body temperature and thermal conductance were typical of those of other birds and they had a typical endothermic response to low ambient temperature. Huddling yielded significant energy savings at low temperatures and a roost nest created a microclimate that buffered against low temperatures. Low basal energy requirements, communal roosting and the insulation of a roost nest confer sufficient energetic benefits, allowing babblers tomeet energy requirements without resorting to heterothermia, even in their depauperate, low-productivity landscape, suggesting that passerine birds use alternatives to torpor to balance their energy budgets when possible.